Information theoretical approach to discovering solar wind drivers of the outer radiation belt. Issue 10 (1st October 2016) - Wing, Simon; Johnson, Jay R.; Camporeale, Enrico; Reeves, Geoffrey D.
Abstract: The solar wind‐magnetosphere system is nonlinear. The solar wind drivers of geosynchronous electrons with energy range of 1.8–3.5 MeV are investigated using mutual information, conditional mutual information (CMI), and transfer entropy (TE). These information theoretical tools can establish linear and nonlinear relationships as well as information transfer. The information transfer from solar wind velocity ( V sw ) to geosynchronous MeV electron flux ( Je ) peaks with a lag time of 2 days. As previously reported, Je is anticorrelated with solar wind density ( n sw ) with a lag of 1 day. However, this lag time and anticorrelation can be attributed at least partly to the Je ( t + 2 days) correlation with V sw ( t ) and n sw ( t + 1 day) anticorrelation with V sw ( t ). Analyses of solar wind driving of the magnetosphere need to consider the large lag times, up to 3 days, in the ( V sw, n sw ) anticorrelation. Using CMI to remove the effects of V sw, the response of Je to n sw is 30% smaller and has a lag time < 24 h, suggesting that the MeV electron loss mechanism due to n sw or solar wind dynamic pressure has to start operating in < 24 h. n sw transfers about 36% as much information as V sw (the primary driver) to Je . Nonstationarity in the system dynamics is investigated using windowed TE. When the data are ordered according to transfer entropy value, it is possible to understand details of the triangle distribution that has been identified between Je ( t + 2 days) versus V sw ( t ). Key Points: Given V sw, the geosynchronous MeV electron response lag time to nsw is < 24 h Transfer entropy can be used to detect changes in the solar wind‐radiation belt system dynamics V sw anticorrelates with nsw with a lag of 14‐17 h, but the lag time has yearly variation